ANALISIS USAHATANI SAYURAN ORGANIK PADA POLA TANAM POLIKULTUR (STUDI KASUS DI WIGUNA FARM, KABUPATEN BOGOR) - Oktri Nanda Rahmawati; Harianto Harianto; Yusalina Yusalina (AGRICA, 2026)
The increasing demand for organic vegetables has opened up great opportunities for producers, including Wiguna Farm. However, Wiguna Farm has not been able to meet all market demand, so efforts to increase production are needed. In addition, Wiguna Farm has not calculated the income level for each type of vegetable cultivated using the polyculture method, even though this information is important as a basis for decision-making for business scale development. Based on this, this study aims to analyze the income level and cost-to-income ratio (R/C ratio) of six types of organic vegetables cultivated at Wiguna Farm using the polyculture method. This study uses a case study method with data collection techniques through interviews and observations, while the research location is determined purposively. The analysis used includes yield analysis, income analysis, and R/C ratio analysis. The results show that the six types of organic vegetables cultivated using the polyculture system at Wiguna Farm are profitable. Among the six commodities, pakcoy has the highest income level and R/C ratio, while kale has the lowest value.